The Private Finance Initiative(PFI)in schools: the experiences of users - Ismail, Suhaiza; Pendlebury, Maurice (Blackwell Publishing, 2006)
he Private Finance Initiative (PFI) offers an alternative to the conventional procurement of public sector infrastructure. Typically under a PFI contract, a consortium of private sector organisations is responsible for designing, building, financing and operating buildings and facilities and associated services that are then used by a public sector organisation for the period of the contract, normally 25 to 30 years. A PFI contract is regarded as the provision of a bundle of services which are paid for year by year by the public sector user, rather than the provision of assets. Since the UK's introduction of the PFI in the early 1990s it has become a widely adopted means of acquiring asset based public services, with over 600 projects entered into by April 2004.1 However, before a PFI contract can be approved it has to be demonstrated that the project will provide value for money (VFM).